2018
DOI: 10.1136/bmjqs-2018-008219
|View full text |Cite
|
Sign up to set email alerts
|

Sicker patients account for the weekend mortality effect among adult emergency admissions to a large hospital trust

Abstract: ObjectiveTo determine whether the higher weekend admission mortality risk is attributable to increased severity of illness.DesignRetrospective analysis of 4 years weekend and weekday adult emergency admissions to a university teaching hospital in England.Outcome measures30-day postadmission weekend:weekday mortality ratios adjusted for severity of illness (baseline National Early Warning Score (NEWS)), routes of admission to hospital, transfer to the intensive care unit (ICU) and demographics.ResultsDespite si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 21 publications
2
28
1
Order By: Relevance
“…A lack of co-morbidities in the data necessitated the use of the abovementioned risk categories to assess illness severity. While some have found a weekend effect regardless of illness severity [38], others showed the effect to be caused by sicker patients at the weekend [39]. Notwithstanding, the effect of disease severity is offset by the magnitude of this study population.…”
Section: Limitations Of This Studymentioning
confidence: 71%
“…A lack of co-morbidities in the data necessitated the use of the abovementioned risk categories to assess illness severity. While some have found a weekend effect regardless of illness severity [38], others showed the effect to be caused by sicker patients at the weekend [39]. Notwithstanding, the effect of disease severity is offset by the magnitude of this study population.…”
Section: Limitations Of This Studymentioning
confidence: 71%
“…This is an interesting inversion of the finding by several other groups that the higher mortality observed on weekends (the so-called weekend effect) reflects increased severity of illness among patients seeking care on weekends 12–15. In other words, these studies have suggested that increased hospital mortality on weekends results from increases in risk of bad outcomes (ie, having sicker patients), not delays in care due to inadequate staffing or other quality problems potentially present on weekends.…”
mentioning
confidence: 69%
“…A detailed case-record review study comparing quality of care and outcomes for patients in two epochs, before (2012–2013) and after (2016–2017) health policy changes to promote 7-day services,19 will appear shortly. However, we already know that there does not appear to be a relationship between weekend consultant staffing and outcomes20 or 7-day service standards,21 that weekend admissions tend to be more acutely ill,12–15 that fewer patients are admitted at weekends despite the same numbers of patients attending hospital emergency departments12 22 and that there is a marked reduction in the proportion of patients referred to hospital by their general practitioners 12 22. The search for the cause of the weekend effect clearly needs to include community services, but Jayawardana and colleagues provide a timely reminder that it is the whole patient pathway which is of interest, not just isolated segments.…”
mentioning
confidence: 99%
“…If, for instance, elevated mortality during off-hours entirely reflected higher severity of illness, this would not necessarily be an ‘off-hours effect’ in the sense that the term usually generates debate. Potential selection bias may explain some of the excess mortality associated with off-hours admissions, where routinely collected in-patient administrative data may not be able to fully account for severity of illness 12 23. Some have made this argument based on the observed lower volume of patients admitted from the community and accident and emergency department (A&E) at weekends, as well as the observed higher proportions of patients admitted during off-hours arriving by ambulance (proxy for severity of illness), among a patient population admitted in an emergency after attending A&E 11 24…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the degree to which elevated mortality for patients admitted at weekends and nights reflects poorer quality of care (ie, ‘off-hours effect’) is a contentious issue 10. Some have argued that higher mortality for weekend or night-time admissions reflects increased severity of illness, and that in-patient administrative data may not be able to fully account for this 11 12…”
Section: Introductionmentioning
confidence: 99%